1982
DOI: 10.1084/jem.156.3.822
|View full text |Cite
|
Sign up to set email alerts
|

H-2-controlled suppression of T cell response to lactate dehydrogenase B. Characterization of the lactate dehydrogenase B suppressor pathway.

Abstract: Over the past few years, considerable progress has been made in the identification of regulatory T cell pathways and factors that act as mediators between T cell subsets involved in these pathways (1-3). However, at least two important aspects of regulation of the immune response have remained largely unexplored. One of them is the role of antigen presentation and of major histocompatibility complex (MHC)1 restriction in the activation of suppressor T (Ts) cells. From the paucity of reports on MHC restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

1982
1982
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…The third mechanism for the specific unrespon siveness is due to the induction of Ts cells by the anti gen [14][15][16][17][18][19] [25], Suppressor epitopes presented by LR class II molecules induce LR-haplotype-restricted Ts cells which suppress only the LRhaplotype-restricted but not HR-haplotype-restricted F, Th cell subsets, although the existence of Ts cells in F| mice is not directly demonstrated in the present study. This possibility has been examined and dis cussed in several other reports [8,26,27], where re sponsiveness to Ir-gene-controlled antigens was dom inant.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The third mechanism for the specific unrespon siveness is due to the induction of Ts cells by the anti gen [14][15][16][17][18][19] [25], Suppressor epitopes presented by LR class II molecules induce LR-haplotype-restricted Ts cells which suppress only the LRhaplotype-restricted but not HR-haplotype-restricted F, Th cell subsets, although the existence of Ts cells in F| mice is not directly demonstrated in the present study. This possibility has been examined and dis cussed in several other reports [8,26,27], where re sponsiveness to Ir-gene-controlled antigens was dom inant.…”
Section: Discussioncontrasting
confidence: 40%
“…It has been proposed that the ability of class II MHC product to present an tigenic fragment determines the responsiveness of the individuals to the given antigen [9][10][11][12][13]. The other pos sibility is the preferential induction of suppressor T cells that prevents the response to the antigen [14][15][16][17][18][19]. In the present study, we demonstrated that the re sponse to ALA is under the control of H-2-linked Ir gene and that the unresponsiveness to ALA is due to the induction of specific suppressor T cells in certain mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…An immune response to pork insulin is observed only after amputation of the pork insulin-specific suppressor limb. A similar situation was described by Baxevanis and associate (8) in which T cells from primed nonresponder strains developed proliferative responses to LDHa in vitro only after addition of antibodies that specifically blocked the suppressor pathway or after removal of Lyt-2-bearing Ts cells. Collectively, these studies suggest that H-2-linked Ir gene control of immune responses is the net result of the stimulation of a variety of T cell subsets and that "holes" in the functional repertoire of Th cells can be mediated by the dominant activity of Ts cells.…”
Section: Discussionmentioning
confidence: 76%
“…Although H-2 restriction of DH has been illustrated in vivo in a transfer system similar to I-A+ and CD4+ Cells Required for Mannan Suppression that employed here for the demonstration of suppressor ac tivity [26], we know of no other papers in which FI-2 re striction of down-regulatory activity has been illustrated in vivo by lymphoid transfer experiments. Clearly, H-2 restric tion of various activities associated with 13 cell suppression has been illustrated in vitro with suppressor cells generated in vivo [48][49][50], but the genetically restricted activity was involved in the effector phase of the response rather than the inductive phase. Genetically restricted activities involving contact sensitivity have also been described [51], but in this case the need for compatible accessory cells was investigat ed at the level of the third-order suppressor cell, not the firstorder inducer-suppressor cell.…”
Section: Discussionmentioning
confidence: 99%